2008
DOI: 10.1111/j.1365-2966.2008.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Education, credentials, and immigrant earnings

Abstract: Using 1981Using to 2001 Census data, we study how the human capital of immigrants is rewarded in Canada. We distinguish between years of schooling and degrees obtained in order to estimate 'sheepskin' effects -the gain in earnings associated with receipt of a degree, controlling for years of schooling. We find that immigrant years of schooling and immigrant work experience accumulated before arrival is valued much less than Canadian experience of comparable natives. However, for immigrants the increase in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
155
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(177 citation statements)
references
References 21 publications
14
155
0
8
Order By: Relevance
“…It should be distinguished from a number of concepts used in the second language acquisition 1 Aydemir, Chen, and Corak (2009a,b) use the 2001 version of these data to study second generation Canadians, while Riddell (2008), andSchaasfma andSweetman (2001) use similar public use versions on earlier years to offer evidence of earnings and age at arrival. Ferrer, Green, and Riddell (2006) also examine issues associated with age at arrival from other surveys.…”
mentioning
confidence: 99%
“…It should be distinguished from a number of concepts used in the second language acquisition 1 Aydemir, Chen, and Corak (2009a,b) use the 2001 version of these data to study second generation Canadians, while Riddell (2008), andSchaasfma andSweetman (2001) use similar public use versions on earlier years to offer evidence of earnings and age at arrival. Ferrer, Green, and Riddell (2006) also examine issues associated with age at arrival from other surveys.…”
mentioning
confidence: 99%
“…Previous research contrasting differences between INV and DNV in a U.S. survey of 214 new ventures found the entrepreneurial teams of INV exhibited higher levels of previous international experience (McDougall, Oviatt, and Shrader 2003). A recent Canadian study indicated that immigrant work experience in their countries of origin is valued much less than the experience of comparable natives (Ferrer and Riddell 2008). This lower return on educational investment in traditional employment might push immigrants to consider starting their own international venture.…”
Section: Capitalising Experiencementioning
confidence: 99%
“…Immigrants are on average more highly educated than natives (Baker and Benjamin 1994) with more years of schooling (Ferrer and Riddell 2008), probably due to the country's immigration selection criteria. American research has also concluded that immigrants and immigrant children are likely to have higher educational aspirations than natives (Vernez and Abrahamse 1996).…”
Section: Capitalising Educationmentioning
confidence: 99%
“…Limited transferability could arise when foreign skills are of a lower quality or with different relevance in the labour markets in the destination country. This may be obvious in the case of language skills, but appears to be the case as well for skills acquired on-the-job or through formal education (e.g., Chiswick 1978;Chiswick and Miller 2009;Duleep and Regets 1999;Friedberg 2000;Ferrer and Riddell 2008;Ferrer, Green and Riddel 2006;Hartog 2000).…”
Section: Theory and Previous Evidencementioning
confidence: 99%